Comparison of Image Quality and Radiation Dose Between Single-Energy and Dual-Energy Images for the Brain With Stereotactic Frames on Dual-Energy Cerebral CT - Zhao, Xiaojing; Chao, Wang; Shan, Yi; Li, Jingkai; Zhao, Cheng; Zhang, Miao; Lu, Jie (Frontiers in Radiology, 2022)
Background: Preoperative stereotactic planning of deep brain stimulation (DBS) using computed tomography (CT) imaging in patients with Parkinson's disease (PD) is of clinical interest. However, frame-induced metal artifacts are common in clinical practice, which can be challenging for neurosurgeons to visualize brain structures. Objectives: To evaluate the image quality and radiation exposure of stereotactic frame brain CT patients acquired using a dual-source CT (DSCT) system in single- and dual-energy modes. Materials and methods: We included 60 consecutive patients with Parkinson's disease (PD) and randomized them into two groups. CT images of the brain were performed using DSCT (group A, 80/Sn150 kVp dual-energy mode; group B, 120 kVp single-energy mode). One set of single-energy images (120 kVp) and 10 sets of virtual monochromatic images (50-140 keV) were obtained. Subjective image analysis for overall image quality using five-point Likert scales. For objective image quality evaluation, CT values, image noise, signal-to-noise ratio (SNR), and contrast-to-noise (CNR) were calculated. The radiation dose was recorded for each patient. Results: The mean effective radiation dose was reduced in the dual-energy mode (1.73 mSv±0.45 mSv) compared to the single-energy mode (3.16 mSv±0.64 mSv) (P< .001). Image noise was reduced by 46%-52% for 120-140 keV VMI compared to 120 kVp images (both P< .01). CT values were higher at 100-140 keV than at 120 kVp images. At 120-140 keV, CT values of brain tissue showed significant differences at the level of the most severe metal artifacts (all P< .05). SNR was also higher in the dual-energy mode 90-140 keV compared to 120 kVp images, showing a significant difference between the two groups at 120-140 keV (all P< .01). The CNR was significantly better in group A for 60-140 keV VMI compared to group B (both P< .001). The highest subjective image scores were found in the 120 keV images, while 110-140 keV images had significantly higher scores than 120 kVp images (all P< .05). Conclusion: DSCT images using dual-energy modes provide better objective and subjective image quality for PD patients at lower radiation doses compared to single-energy modes and facilitate brain tissue visualization with stereotactic frame DBS procedures.